TP53, a gene for colorectal cancer predisposition in the absence of Li-Fraumeni-associated phenotypes. Issue 6 (30th September 2020) - Terradas, Mariona; Mur, Pilar; Belhadj, Sami; Woodward, Emma R; Burghel, George J; Munoz-Torres, Pau M; Quintana, Isabel; Navarro, Matilde; Brunet, Joan; Lazaro, Conxi; Pineda, Marta; Moreno, Victor; et al.
Abstract : Objective: Germline TP53 pathogenic (P) variants cause Li-Fraumeni syndrome (LFS), an aggressive multitumor-predisposing condition. Due to the implementation of multigene panel testing, TP53 variants have been detected in individuals without LFS suspicion, for example, patients with colorectal cancer (CRC). We aimed to decipher whether these findings are the result of detecting the background population prevalence or the aetiological basis of CRC. Design: We analysed TP53 in 473 familial/early-onset CRC cases and evaluated the results together with five additional studies performed in patients with CRC (total n=6200). Control population and LFS data were obtained from Genome Aggregation Database (gnomAD V.2.1.1) and the International Agency for Research on Cancer (IARC) TP53 database, respectively. All variants were reclassified according to the guidelines of the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP), following the ClinGen TP53 Expert Panel specifications. Results: P or likely pathogenic (LP) variants were identified in 0.05% of controls (n=27/59 095) and 0.26% of patients with CRC (n=16/6200) (p<0.0001) (OR=5.7, 95% CI 2.8 to 10.9), none of whom fulfilled the clinical criteria established for TP53 testing. This association was still detected when patients with CRC diagnosed at more advanced ages (>50 and>60 years) were excluded from the analysis to minimise the inclusion of variants caused by clonal haematopoiesis. Loss-of-function and missense variants were strongly associated with CRC as compared with controls (OR=25.44, 95% CI 6.10 to 149.03, for loss of function and splice-site alleles, and OR=3.58, 95% CI 1.46 to 7.98, for missense P or LP variants). Conclusion: TP53 P variants should not be unequivocally associated with LFS. Prospective follow-up of carriers of germline TP53 P variants in the absence of LFS phenotypes will define how surveillance and clinical management of these individuals should be performed.